MCSE Test Success: NT Server 4 in the Enterprise Exam 70-068 - Donald, Lisa (SYBEX Inc., 1998)
This book is the key to passing Exam 70-068, implementing and supporting Microsoft Windows NT Server 4.0 in the Enterprise.
Keywords: Computer Operating Systems Window Server; Non-Fiction